A simple and efficient in vitro method for metabolism studies of radiotracers - Lee, SY; Choe, YS; Kim, DH; Park, BN; Kim, SE; Choi, Y; Lee, KH; Lee, JW; Kim, BT (ELSEVIER SCIENCE INC, 2001)
In vitro metabolism of acetylcholinesterase inhibitors containing 3-[F-18]fluoromethylbenzyl-([F-18]1) and 4-[F-18]fluorobenzyl-piperidine moieties ([F-18]2) was studied and compared with the in vivo metabolism. Defluorination of the [F-18]1 mainly occurred to generate [F-18]fluoride ion both in vitro and in vivo, In contrast, the [F-18]2 was converted into an unknown polar metabolite in both metabolism methods and another metabolite, 4-[F-18]fluorobenzoic acid in vitro. These results demonstrated that the in vitro method can be used to predict the in vivo metabolism of both radiotracers. (C) 2001 Elsevier Science Inc. All rights reserved.
Keywords: F-18